Research methods in geography : a critical introduction - Gomez, Basil; Jones, John Paul, 1955- (Chichester, West Sussex, U.K. : Wiley-Blackwell, 2010)
This comprehensive textbook offers a conceptual and practical introduction to research methodology, data collection, and techniques used in both human and physical geography. It explores a full range of contemporary geographic techniques, including statistics, mathematical analysis, GIS, and remote sensing.
Includes bibliographical references and index.
Keywords: Geography -- Research -- Methodology